PENGARUH PENGGUNAAN MEDIA FLASH CARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS I - Mariana Juni Indah Sundari; Sri Handayani; Elinda Rizkasari (Widya Wacana: Jurnal Ilmiah, 2023)
The purpose of this study was to determine the effect of using flash card media on the initial reading ability of class I students at SDN Tugu Jebres No.120 Surakarta in the academic year 2022/2023. This research was conducted at SDN Tugu Jebres No.120 Surakarta. The subjects in this study were class I students, totaling 28 students. The method used is experimental research type one group pretest posttest design. The data analysis technique used was descriptive analysis by comparing the results of the initial reading ability between the pretest and posttest. Data collection techniques used in this study were tests, observation and documentation. Judging from the hypothesis test with the Paired Sample t-test formula, it is obtained that tcount = 14.165 and ttable with d.b = so = 27 this value can be compared with the ttable value at a significant level of 5%, namely 2.052. So tcount > ttable or 14.165 > 2.052 which means Ho is rejected and Ha is accepted. Keywords: Flash Card Media, Initial Reading Ability